Pseudomonas fluorescens NZI7 repels grazing by C. elegans, a natural predator. - Burlinson, P; Studholme, D; Cambray-Young, J; Heavens, D; Rathjen, J; Hodgkin, J; Preston, G (2013)
The bacteriovorous nematode Caenorhabditis elegans has been used to investigate many aspects of animal biology, including interactions with pathogenic bacteria. However, studies examining C. elegans interactions with bacteria isolated from environments in which it is found naturally are relatively scarce. C. elegans is frequently associated with cultivation of the edible mushroom Agaricus bisporus, and has been reported to increase the severity of bacterial blotch of mushrooms, a disease caused by bacteria from the Pseudomonas fluorescens complex. We observed that pseudomonads isolated from mushroom farms showed differential resistance to nematode predation. Under nutrient poor conditions, in which most pseudomonads were consumed, the mushroom pathogenic isolate P. fluorescens NZI7 was able to repel C. elegans without causing nematode death. A draft genome sequence of NZI7 showed it to be related to the biocontrol strain P. protegens Pf-5. To identify the genetic basis of nematode repellence in NZI7, we developed a grid-based screen for mutants that lacked the ability to repel C. elegans. The mutants isolated in this screen included strains with insertions in the global regulator GacS and in a previously undescribed GacS-regulated gene cluster, 'EDB' ('edible'). Our results suggest that the product of the EDB cluster is a poorly diffusible or cell-associated factor that acts together with other features of NZI7 to provide a novel mechanism to deter nematode grazing. As nematodes interact with NZI7 colonies before being repelled, the EDB factor may enable NZI7 to come into contact with and be disseminated by C. elegans without being subject to intensive predation.